Na`ar¥yOEt al-îukm and Ma§OEdir al-Shar¥`ah (American Journal of Islam and Society, 2008)
On 17 October 2008, the Academy of Islamic Studies held its first seminaron Na`ar¥yOEt al-îukm and Ma§OEdir al-Shar¥`ah (NAZMAS1/2008) at theUniversity of Malaya, Kuala Lumpur, Malaysia. We would like to thank allof the lecturers and students of the Department of Shari`ah and Law, especiallyAhmad Hidayat Buang (dean of the Apium) and Siti Mashitoh btMahamood (head, Department of Shari`ah and Law), for their support andencouragement.The seminar originally sought to bring together students, researchers, andscholars interested in Islamic law studies from all over the world. Due to thelimited time available for academicians and scholars to prepare their papers,as well as holding it right after Ramadan, however, was the event to be scaleddown to a local seminar limited to the Academy of Islamic Studies,University of Malaya. It was, nevertheless, a highly fruitful and successfulevent.Given the international focus on Islamic studies and law, the seminarwas structured around the fundamental principles of Islamic law and howthey can be embraced by elaborating upon their vital principles to makethem better understood.After the chairmen’s introductory remarks, seminar director Saim Kayadibi(senior lecturer, Department of Shari`ah and Law) gave an openingspeech that emphasized the importance of studying the Shari`ah’s fundamentalprinciples and how the seminar could make a constructive contributionto advancing the participants’ knowledge and understanding of the innerdimension of the aúkOEm and ma§OEdir al-Shar¥`ah. Mahamood then openedthe seminar ...